2018
DOI: 10.1111/1755-6724.13548
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the Iron–rich Melt in the Heijianshan Iron Deposit, Eastern Tianshan, NW China: Insights into the Origin of Volcanic Rock–hosted Iron Deposits

Abstract: Long‐standing controversy persists over the presence and role of iron–rich melts in the formation of volcanic rock‐hosted iron deposits. Conjugate iron–rich and silica–rich melt inclusions observed in thin‐sections are considered as direct evidence for the presence of iron‐rich melt, yet unequivocal outcrop‐scale evidence of iron‐rich melts are still lacking in volcanic rock‐hosted iron deposits. Submarine volcanic rock‐hosted iron deposits, which are mainly distributed in the western and eastern Tianshan Moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Accordingly, this study identified the primitive sedimentary type and hydrothermally altered type of high-grade iron ore from the ore texture, structure, and geochemical characteristics. Although the detailed alteration process and mechanism are not clear, we preliminarily suggest that the genesis of high-grade ores is probably related to the hydrothermal process of migmatization, which may lead to the desilication of adjacent BIFs [14].…”
Section: Genesis Of High-grade Iron Oresmentioning
confidence: 90%
See 1 more Smart Citation
“…Accordingly, this study identified the primitive sedimentary type and hydrothermally altered type of high-grade iron ore from the ore texture, structure, and geochemical characteristics. Although the detailed alteration process and mechanism are not clear, we preliminarily suggest that the genesis of high-grade ores is probably related to the hydrothermal process of migmatization, which may lead to the desilication of adjacent BIFs [14].…”
Section: Genesis Of High-grade Iron Oresmentioning
confidence: 90%
“…In addition, most large iron ore deposits, such as Gongchangling, Nanfen, Xingshan and Sijiaying [8], contain a certain number of high-grade iron ore resources. High-grade iron ore mainly includes two types (primitive sedimentary and hydrothermally altered); however, the hydrothermal origins are still controversial, with origins mainly in metamorphic hydrothermal or migmatized hydrothermal environments [9][10][11][12][13][14]. Many geologists constrain the metallogenic age of BIF volcanic interbeds based on their zircon ages.…”
Section: Introductionmentioning
confidence: 99%